Die Kommission als Einziehungsbehörde von Vertragsverletzungsstrafen und ihre Kontrolle durch die Unionsgerichte - Schramm, Tobias (Zeitschrift für europarechtliche Studien, 2025)
The Commission is responsible for recovering financial penalties imposed on Member States by the Court of Justice for persistent infringements. Firstly, in order to fix the amount payable (in particular, in penalty payments), it must determine when the Member State remedied the breach of Union law. In doing so, the Commission must formally examine whether a measure was taken to remedy the infringement. If a Member State brings an action before EU courts against the Commission's assessment, it bears the secondary burden of setting out and proving that the assessment is incorrect. Conversely, the Commission may not review on substantive grounds whether the Member State’s remedial measure conforms with Union law, since only the CJEU has that jurisdiction. The Commission can, however, establish the obvious inadequacy of the remedial measure. In a second step, the Commission can decide to offset the sanction debt against claims of the Member State against the Union if the Member State refuses to pay even after the amount payable has been determined. This can also be appealed to the EU courts, who have rightly confirmed such offsetting in principle, despite objections from the literature.
CRIS-Team Scopus Importer:2025-11-28
Keywords: Burden of proof; Enforcement; Execution of CJEU judgments; Financial penalties; Infringement proceedings; Law governing the institutions; Non-compli-ance; Recovery; Rule of Law; Set-off